Factors Affecting Sleep Quality of Treated Patients in the Intensive Cardiac Care Unit Room - Nyayu Nina Putri Calisanie; Hemel Prayoga (STIKep PPNI Jawa Barat, 2023)
Aims: ICCU (Intensive Cardiac Care Unit) is a special room provided in a hospital that treats patients with cardiovascular system problems. Sleep disturbance is one of the significant problems that occur in patients during treatment in the intensive cardiac care unit. Patients in the ICCU are at risk of experiencing sleep disturbances due to various procedures and monitor sounds, noise from communication between staff or noise, sleep disturbances related to lighting, complaints of pain and treatment procedures that occur in >50% of intensive care units. This causes the patient's healing process to be hampered. This study aims to find out factors affecting sleep quality of patients treated in ICCU. Methods: This research is a quantitative correlational analytic research approach cross sectional study, conducted at a Dustira Tk II Hospital in July-August 2022, the number of samples was 23 respondents. The instruments used included a questionnaire. Results: There is a relationship between pain and sleep quality with a Pvalue of 0.001. There is a relationship between the environment and sleep quality with a Pvalue of 0.006. There is no relationship between medication and sleep quality with a Pvalue of 0.097. There is no relationship between anxiety and sleep quality with a Pvalue of 0.082. S-regression analysis regarding the factor that most influences the sleep quality of ICCU patients is the factor of pain complaints with a P value of 0.036. Conclusion: There is a significant relationship between physical complaints and environmental factors on the sleep quality of patients at the Dustira Hospital ICCU. The factor that most influences the quality of sleep is the factor of pain complaints.